Asset Governance Information System Design at PT. Andalan Kreatif Utama by using QRCode (Quick Response Code) labelling technique - Fadli Emsa Silmi; Muhammad Fitra Wahyudin; Titi Widaretna (Politeknik Mardira Indonesia, 2024)
Quick response code (QR Code) is a type of matrix code or two-dimensional barcode developed by Denso, QR Code easily helps us store all types of data, such as numeric data and alphabetic data. PT. Andalan Kreatif Utama is a company in the field of providing goods and services for security system equipment and fiber. Asset governance activities at PT. The Andalan Kreatif Utama is done using form paper then input through excel sheets by GA (General Affair). This makes GA (general affair) difficult in recording company assets, knowing age, difficulty knowing the position or location of company assets and difficulties when there is a process of replacing damage and loss of assets. The purpose of this study is to create an application that can provide information from the many assets contained in PT. Andalan Kreatif Utama and streamline and streamline the search for asset information by scanning the QR Code on the item and the web will display the results in realtime. The system development method used is Object Oriented Programming (OOP), OOP is an object-oriented programming method. Various interrelated objects will be arranged into a group known as classes. These various objects will interact with each other in order to solve complex program problems. The expected result of this study is that the implementation of asset labeling using QRcode can run optimally.